SARS-CoV-2 Induces Cytokine Responses in Human Basophils - Bonam, Srinivasa Reddy; Chauvin, Camille; Levillayer, Laurine; Mathew, Mano Joseph; Sakuntabhai, Anavaj; Bayry, Jagadeesh (Frontiers in Immunology, 2022)
Basophils play a key role in the orientation of immune responses. Though the interaction of SARS-CoV-2 with various immune cells has been relatively well studied, the response of basophils to this pandemic virus is not characterized yet. In this study, we report that SARS-CoV-2 induces cytokine responses and in particular IL-13, in both resting and IL-3 primed basophils. The response was prominent under IL-3 primed condition. However, either SARS-CoV-2 or SARS-CoV-2-infected epithelial cells did not alter the expression of surface markers associated with the activation of basophils, such as CD69, CD13 and/or degranulation marker CD107a. We also validate that human basophils are not permissive to SARS-CoV-2 replication. Though increased expression of immune checkpoint molecule PD-L1 has been reported on the basophils from COVID-19 patients, we observed that SARS-CoV-2 did not induce PD-L1 on the basophils. Our data suggest that basophil cytokine responses to SARS-CoV-2 might help in reducing the inflammation and also to promote antibody responses to the virus.